Cultural Semiotic Analysis in the Mappacci Tradition, Wedding Customs of the Bugis Tanjungbatu Tribe, Kundur, Karimun Regency, Riau Islands.: Analisis Semiotika Kultural dalam Tradisi Mappacci Adat Pernikahan Suku Bugis Tanjungbatu, Kundur, Kabupaten Karimun, Kepulauan Riau - Aida; Ahada Wahyusari; Zaitun; Suhardi; Abdul Malik; Tessa Dwi Leoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to describe the forms of icons, indices and symbols in the mappacci tradition mantra found in Lubuk Village, Tanjungbatu, Kundur, Karimun Regency, Riau Islands. The object of this research is the mantra in the mappacci tradition of Lubuk Village, Tanjungbatu Kundur, Karimun Regency, Riau Islands, which was obtained from informants. This research method is descriptive using a qualitative approach. The data collection techniques used were interviews and recording. Data analysis techniques are carried out using data collection techniques, data reduction, data presentation, and drawing conclusions. The results of data analysis obtained from Cultural Semiotic Analysis in the Mappacci Tradition, Wedding Customs of the Bugis Tribe of Tanjungbatu, Kundur, Karimun Regency, Riau Islands, namely the Mappacci tradition mantra, found the use of semiotics such as icons, indexes and symbols.